Systematic Literature Review: The Influence of Discovery Learning Model on Students' Mathematical Representation Ability - Aulia, Kintan Wanda; Sutiarso, Sugeng (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
The purpose of this Systematic Literature Review (SLR) is to highlight the effectiveness of the Discovery Learning model in improving students' mathematical representation ability. The research process involves the following stages: formulating research objectives, article collection using Publish or Perish 8, article sreening with the inclusion criteria used, and data evaluation where the article that selected were reviewed in depth. The review encompassed studies from various educational settings and consistently demonstrated the positive impact of Discovery Learning on students' ability to represent mathematical concepts and solve problems. The findings underscore the potential of the discovery learning model as a valuable approach to enhance students' mathematical representation ability and pave the way for further research and implementation in educational settings